The impact of COVID-19-related anxiety on obstetric complications and mental health in quarantined pregnant women - Solmaz Heidarifard; Niloofar Khoshnam Rad; Mahsa Khoshnam Rad (BMC Infectious Diseases)
Abstract Introduction The COVID-19 pandemic heightened anxiety among pregnant women, raising concerns about its impact on maternal and fetal health. Although prenatal anxiety is linked to adverse outcomes, the specific relationship between COVID-19-related fear and obstetric complications in quarantined populations remains understudied. This study investigated the association between COVID-19-related fear, obstetric complications, and mental health disorders among quarantined pregnant women in Tehran, Iran. Methods This cross-sectional study (June–December 2020) 52 quarantined pregnant women were recruited via convenience sampling from a Tehran health center. Data were collected through structured telephone interviews using a validated researcher-made questionnaire. The tool assessed demographics, obstetric history, mental health symptoms (e.g., night-time anxiety, sleep disturbances), and COVID-19-related fear via a 0–10 Auditory Analog Scale (AAS). Obstetric complications (e.g., severe vaginal bleeding, chorioamnionitis) were self-reported and clinically verified. Spearman’s rank correlation (non-parametric variables) and Pearson’s correlation (continuous variables) were used, with significance set at p < 0.05. Results Participants (mean age: 29.9 ± 6.47 years; gestational age: 30 ± 11.57 weeks) exhibited high COVID-19 fear (54.5% severe fear). Fear correlated significantly with obstetric complications (r = 0.22, p = 0.007), particularly delayed care-related outcomes such as severe vaginal bleeding (18.8%), chorioamnionitis (8.9%), and reluctance to seek hospitalization (12.5%). Fear also linked to mental health challenges (r = 0.23, p = 0.005), including night-time anxiety (28.9%) and sleep disturbances (32.2%). Weak correlations emerged with occupation (r = 0.23, p = 0.01) and education (r = 0.24, p = 0.02), though effect sizes were modest (R² ≈ 0.05). Conclusion COVID-19-related fear in quarantined pregnant women was associated with obstetric complications (e.g., care avoidance) and mental health disorders (e.g., sleep disturbances). Despite modest correlations, findings underscore the need for antenatal care integrating mental health screening, telehealth support, and culturally sensitive interventions to mitigate pandemic-driven risks to maternal-fetal health.